A New Approach to Enhancing Innovative Work Behavior Involves Utilizing Psychological Empowerment as a Mediator - Hasbi, Fikri; Herri; Lukito, Hendra (SAFE-Network, 2023)
The aim of this study is to examine and analyze the role of psychological empowerment as a mediator in the influence of support for innovation and leader-member exchange on innovative work behavior among employees of Bank Nagari in Padang City. The population for this study consisted of all Marketing and IT employees of Bank Nagari in Padang City, totaling 101 individuals. The sample was selected using Isaac and Michael's sampling method, resulting in a sample size of 78 individuals. The analytical methods employed in this study were descriptive statistical analysis and factor description analysis using SmartPLS 4.0 software. The findings of the study indicate that support for innovation does not have a significant influence on employees' innovative work behavior. However, support for innovation has a positive and significant impact on employees' psychological empowerment. Furthermore, leader-member exchange does not have a significant influence on employees' innovative work behavior, but it does have a positive and significant impact on employees' psychological empowerment. Psychological empowerment, in turn, has a positive and significant influence on employees' innovative work behavior. Additionally, psychological empowerment mediates the relationship between support for innovation and employees' innovative work behavior, as well as the relationship between leader-member exchange and employees' innovative work behavior at Bank Nagari in Padang City.